Decentralized or collective bargaining in a strategy experiment - Siegfried Berninghaus; Werner Güth; Claudia Keser (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
We present an experiment where two players bargain with a third player. They can bargain either separately or form a joint venture to bargain collectively. Our theoretical benchmark solution predicts decentralized bargaining, as only one player has an interest in forming a joint venture. However, we observe a significant amount of collective bargaining. Collective bargaining, when compared with decentralized bargaining, has no significant effect on the payoffs of the players in the joint venture but reduces the payoff of the third player.
urn:nbn:de:kobv:11-10046770
Keywords: 330; Bargaining; Joint Venture; Merger; Experiments; Equilibrium Selection